2019
DOI: 10.1002/advs.201901410
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Molybdenum Selenide Nanosheet as an Efficient Trap for the Permanent Sequestration of Vapor‐Phase Elemental Mercury

Abstract: The key challenge of vapor‐phase elemental mercury (Hg0) sequestration is the rational design of a sorbent with abundantly available ligands that exhibit excellent affinity toward Hg0 to simultaneously achieve a high uptake capacity and rapid capture rate. In this work, it is demonstrated how the correct combination of functional ligands and structural properties can form an ideal remediator for permanent Hg0 immobilization. The adsorption capacity of an amorphous molybdenum triselenide (MoSe3) nanosheet great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…8,17 As a result, preparation of amorphous nanomaterials with 2D morphology, which could benefit from both 2D and amorphous structures, provides an effective route to boost their performance in various applications. Until now, research efforts have greatly enriched the family of 2D amorphous nanomaterials, such as metals, 40 metal oxides, 41 metal hydroxides, 42 sulfides, 43 selenides, 44 and so forth. In the following sections, some representative examples of newly emerged 2D amorphous nanomaterials are discussed.…”
Section: D Amorphous Nanomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…8,17 As a result, preparation of amorphous nanomaterials with 2D morphology, which could benefit from both 2D and amorphous structures, provides an effective route to boost their performance in various applications. Until now, research efforts have greatly enriched the family of 2D amorphous nanomaterials, such as metals, 40 metal oxides, 41 metal hydroxides, 42 sulfides, 43 selenides, 44 and so forth. In the following sections, some representative examples of newly emerged 2D amorphous nanomaterials are discussed.…”
Section: D Amorphous Nanomaterialsmentioning
confidence: 99%
“…Other 2D Amorphous Nanomaterials Other 2D nanomaterials with amorphous phase have also been synthesized, including metal sulfides, 43 metal selenides, 44 carbon, 49 phosphorus, 55 etc. For example, Zhou et al reported the facile preparation of amorphous VS 2 nanosheets by treating the VS 2 bulk crystals with supercritical CO 2 .…”
Section: D Amorphous Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mercury (Hg), known for its transportability and persistence, is of great environmental concern as a toxin that causes birth defects and neurological impairments in humans. According to the Global Mercury Assessment released by the United Nation Environment Programme (UNEP) in 2018, the estimated median for anthropogenic Hg emission worldwide reached 2500 tons annually, increasing by approximately 500 tons within 10 years . Among various anthropogenic sources accounting for Hg emissions, the coal combustion process is one of the largest single-known sources and primarily discharges the elemental form of mercury (Hg 0 ) due to its high volatility and insolubility in water. Considering the expansive scale of energy demands worldwide, the Minamata Convention came into force in 2017, aiming to strictly control Hg emissions in its 128 signatories with an emphasis on coal combustion power plants. , To fulfill the Convention, effectively degrading Hg 0 from stationary sources is the key challenge, which is expected to relieve the environment from heavy Hg 0 contaminations.…”
Section: Introductionmentioning
confidence: 99%
“…As an immediate response to the forces of the Minamata Convention and the defects of AC techniques, mineral selenides have been recently found as potential alternatives to traditional AC sorbents for Hg 0 capture from various industrial processes. , The mineral selenides significantly outperformed traditional ACs because (1) mineral selenides are adequately covered by active selenide sites that are the one of the best-known antidotes against mercury and could achieve extremely high Hg 0 capture performances; and (2) mineral selenides could chemisorb Hg 0 and convert Hg 0 into metabolically inactive mercury selenide (HgSe), which exhibited much lower leachability than Hg 0 adsorbed on ACs by orders of magnitude . Among various mineral selenides, hexagonal copper selenide (CuSe) based sorbent was found as the first example and a potential candidate for efficient and permanent Hg 0 sequestrations.…”
Section: Introductionmentioning
confidence: 99%